Manajemen Kurikulum Pesantren Modern dalam Mengintegrasikan Nilai Keislaman dan Sains di Pondok Pesantren Anwarul Huda Malang - Widodo, Wahyudi (MASALIQ, 2025)
The integration of Islam and science in the modern era is an important part in facing technology and globalization, so the management of the pesantren curriculum must adjust to this. This research aims to discuss the curriculum management of modern Islamic boarding schools in integrating Islamic values and science in the Anwarul Huda Islamic Boarding School Malang. The research method used is qualitative with a descriptive approach. The results of the research show that curriculum management at Anwarul Huda Islamic boarding school Malang starts from the VISION, MISSION and goals. After that, a management structure and programs were formed that integrated Islamic values and science. There are two officially Islamic boarding school programs, and the other is supportive. The official programs are: first, the regular program (special school classes) which is specifically for junior high school or MTS graduates to continue their MA in Islamic boarding schools based on Islam and modern science. Where students at MA are not only taught related to books and religion, but general knowledge and practice that are in accordance with national curriculum standards such as Physics, Biology, Technology and others. Second, a special program called madrasah diniah which is required for students, both in school or college, with a class level. The supporting program is the implementation of activities integrating Islamic and scientific values, for example making chips using modern tools, tempeh beans from original materials, mineral water that is guaranteed to be safe and original, and also maggot and worm cultivation which are all applied based on science and religious science so as to maintain halal and honesty.